Racial and ethnic disparities in psychological care for individuals with FASD: a dis/ability studies and critical race theory perspective toward improving prevention, assessment/diagnosis, and intervention - Madeline N. Rockhold; Blake A. Gimbel; Alesia A. Richardson; Carson Kautz-Turnbull; Emily L. Speybroeck; Erik de Water; Julianne Myers; Emily Hargrove; Maggie May; Samia S. Abdi; Christie L. M. Petrenko (Frontiers Media S.A., 2024)
Fetal alcohol spectrum disorders (FASD) are among the most common neurodevelopmental disorders and substantially impact public health. FASD can affect people of all races and ethnicities; however, there are important racial and ethnic disparities in alcohol-exposed pregnancy prevention, assessment and diagnosis of FASD, and interventions to support individuals with FASD and their families. In this article we use the Dis/Ability Studies and Critical Race Theory (Dis/Crit) framework to structure the exploration of disparities and possible solutions within these three areas (prevention, diagnosis, intervention). Dis/Crit provides a guide to understanding the intersection of dis/ability and race, while framing both as social constructs. Following the Dis/Crit framework, the systemic, historical, and contemporary racism and ableism present in psychological care is further discussed. We aim to elucidate these racial and ethnic disparities within the fields of psychology and neuropsychology through the Dis/Crit framework and provide potential points of action to reduce these disparities.